2008
DOI: 10.1093/rpd/ncn004
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation strategies introduced for CR at health care centres in Estonia

Abstract: In recent years, starting from 2001, conventional film-screen radiography has been rapidly replaced by digital (mostly by computed radiography, CR) techniques in Estonia. New strategies for optimisation and quality assurance for digital radiography have been introduced by the DIMOND III and SENTINEL partners recently. It includes consideration to diagnostic requirements of a given clinical situation, but also objectivation and standardisation of image quality, e.g. using CDRAD test phantom, and constancy testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Our FOM can be useful for optimisation of the x-ray units and imaging protocols. On the other hand, from the reviewed literature on optimisation, it was found that the common FOM formulas that are utilised with LCD detectability and a CD phantom such as CDRAD 2.0 phantom used are FOM=SNR 2 /dose and FOM=CNR 2 /dose [36][37][38]. However, these two formulas use SNR and CNR as a metric which are self-limiting since, as stated, they do not take into account the object size (pathology or anatomical structure) during IQ evaluation [39] which is considered a limitation in these two measures of IQ.…”
Section: Iq Versus Radiation Dose/fommentioning
confidence: 99%
“…Our FOM can be useful for optimisation of the x-ray units and imaging protocols. On the other hand, from the reviewed literature on optimisation, it was found that the common FOM formulas that are utilised with LCD detectability and a CD phantom such as CDRAD 2.0 phantom used are FOM=SNR 2 /dose and FOM=CNR 2 /dose [36][37][38]. However, these two formulas use SNR and CNR as a metric which are self-limiting since, as stated, they do not take into account the object size (pathology or anatomical structure) during IQ evaluation [39] which is considered a limitation in these two measures of IQ.…”
Section: Iq Versus Radiation Dose/fommentioning
confidence: 99%